Can MoCA and MMSE Be Interchangeable Cognitive Screening Tools? A Systematic Review - Siqueira, Glória S. A [UNESP]; Hagemann, Paula De M. S [UNESP]; Coelho, Daniela De S; Santos, Flávia Heloísa Dos [UNESP]; Bertolucci, Paulo H. F; Heyn, Patricia C (Oxford University Press (OUP), 2019)
Background and Objectives: Cognitive disorders may be an early sign of neuropsychiatric disorders; however, it remains unclear whether the screening measures are interchangeable. The aim of this study was to contrast the most commonly used screening tools - Mini-Mental State Examination (MMSE) and Montreal Cognitive Assessment (MoCA) - for early detection of neurocognitive disorder (NCD). Research Design and Methods: This study presents a descriptive systematic review and informative literature according to the Cochrane Foundation's guidelines. The keywords Mini-Mental State Examination and Montreal Cognitive Assessment were searched in the Web of Science, SciELO, and LILACS databases. Results: Fifty-one studies were selected including a total sample of 11,870 participants (8,360 clinical patients and 3,510 healthy controls). Most studies were published in the past 5 years using a cross-sectional design, carried out across the world. They were organized by age ranges (18-69 years and 20-89 years), years of schooling, and mental status (with and without mental and behavior disorders). Sixteen of 18 studies had participants aged 18-69 years, and 21 out of 33 studies within the older set suggested that the MoCA is a more sensitive tool for detecting NCD. Discussion and Implications: Thirty-seven studies suggested that the MoCA is a more sensitive tool for NCD detection because it assesses executive function and visuospatial abilities. Some individuals who demonstrated normal cognitive function on the MMSE had lower performance on the MoCA. However, it seems necessary to establish different cutoffs based on years of schooling to avoid false positives. Future studies should contrast MoCA with other screening tools designed for NCD assessment.
Keywords: Cognition; Mini-Mental State Examination; Montreal Cognitive Assessment; Psychology of aging/psychiatry